Evaluasi Keberlanjutan Sistem Pengelolaan Air Limbah Domestik Terpusat Skala Komunal - Abraham Abraham; Suharyanto Suharyanto (Departement of Mathematics Education, 2023)
In previous research, several Communal SPALD-T/IPAL at SANIMAS Cimahi city were still in a less sustainable status in terms of financing, technical and social aspects. One of them occurred in the SANIMAS RW 10 and 16 Kelurahan Cibabat program which had problems with technical SOPs, community participation and difficult access. While in SANIMAS RW 19 there were problems with the management organization sector that was not optimal. With management conditions like this, challenges in management have also increased because the Indonesian government has implemented various